Preliminary Near-Transfer Effects of a Manualized Cognitive Training Toolkit for Pediatric Cancer Survivors: A Nonrandomized Feasibility Trial - Satapathy, Sujata; Sharma, Renu; Chadha, Mansi; Bakshi, Sameer; Seth, Rachna; Sagar, Rajesh; Khanna, Vidhi; Maurya, Rachana; Devi, Usha; Agarwala, Sandeep; Jain, Vishesh (Indian Journal of Medical and Paediatric Oncology, 2025)
Computerized cognitive training has reasonable evidence for ameliorating cognitive deficits in childhood cancer survivors; however, availability, affordability, and nonadaptation are impending factors. Despite therapist-delivered cognitive training has similar effects, there is no indigenous and replicable structured manualized cognitive training for childhood cancer survivors in India.The feasibility and indicative impact assessment of a manualized cognitive training toolkit (MCTT) (similar effect size as CogMed working memory training and PSSCogRehb software for children with attention deficit hyperactivity disorder) was examined to fabricate to meet the needs of the target group.With a pre–post design, 10 survivors (M = 8, F = 2) between 6 and 11 years (mean age = 8.6 ± 2.7 years) with Social Quotient (SQ) ≥ 85 (mean SQ = 99.8 ± 11.75), and having significant cognitive deficits were recruited. Far-transfer effects were assessed through parents' rated Child Behavior Rating Scale, and near-transfer effects through Cognitive Assessment System-2.Note that 58.33% had cognitive deficits across planning, attention, and successive and simultaneous processing. MCTT with 18 cognitive tasks (16 difficulty levels) delivered in 8 days (over 2 weeks:16 hours) was feasible. Except attention domain, MCTT had significant near-transfer effects on planning (Z = 2.88, p < 0.01, r = 0.86), simultaneous (Z = 2.55, p < 0.01, r = 0.81), and successive processing (Z = 2.45, p < 0.01, r = 0.77) with large effect size.MCTT was a feasible toolkit; however, refabrication with increased number of attention-focused tasks and difficulty levels was indicated. Expectedly, MCTT did not have positive/negative impacts on behaviors.MCTT has potentiality for a randomized controlled trial and can be compared to any computerized training for this target group.
Keywords: MCTT; pediatric cancer survivors; cognitive deficits